Lipid profile analysis of type 2 diabetic patients in Bengaluru population, India - Venkatesh, Shyamala K.; M. V., Sudheer K.; T., Mohana Krishna (International Journal of Research in Medical Sciences, 2018)
Background: Prevalence of Diabetes in India is 69.2 million, among which type 2 diabetes mellitus (T2DM), constitutes for 90% of all the diabetic populations. Previous studies have proved the association of T2DM, with increasing risk of cardiovascular diseases (CVDs) and the level of risk varies among males and females. The present study aims to analyze the lipid profile of T2DM patients and compare the lipid profile of T2DM males and females in Karnataka, Bengaluru population. Methods: The study included 171 T2DM patients, 59 females and 112 males aged 21 years and above. Total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), very low density lipoprotein cholesterol (VLDL-C) and triglycerides (TG) concentrations values were analyzed for each group. Paired students t test was applied to identify the differences in lipid profile values of males and females with T2D. Results: The mean value of TC, VLDL-C and LDL-C were higher in overall T2DM patients than the normal range and HDL-C was lower in T2DM patients. Comparison between males and females showed significantly higher LDL-C in females with T2DM than males. Other lipid parameters TC, TG and HDL-C did not show any significant differences between females and males with T2DM. Conclusions: This study demonstrated the existence of dyslipidemia in T2DM population which is major risk factor for CVD. Greater LDL-C was observed in T2DM females compared to T2DM males suggests higher risk for CVD in females compared to males.